The function of the human homolog of Saccharomyces cerevisiae REV1 is required for mutagenesis induced by UV light - Gibbs, Peter E. M. (The National Academy of Sciences, 2000)
In Saccharomyces cerevisiae, most mutations induced by a wide range of mutagens arise during translesion replication employing the REV1 gene product and DNA polymerase ζ. As part of an effort to investigate mammalian mutagenic mechanisms, we have identified cDNA clones of the human homologs of the yeast REV genes and examined their function in UV mutagenesis. Previously, we described the isolation of a human homolog of yeast REV3, the catalytic subunit of pol ζ, and here report the identification and sequence of a human homolog of yeast REV1. This gene was isolated by identifying an expressed sequence tag encoding a peptide with similarity to the C terminus of yeast Rev1p, followed by sequencing of the clone and retrieval of the remaining cDNA by 5′ rapid amplification of cDNA ends. The human gene encodes an expected protein of 1,251 residues, compared with 985 residues in the yeast protein. The proteins share two amino-terminal regions of ≈100 residues with 41% and 20% identity, a region of ≈320 residues with 31% identity, and a central motif in which 11 of 13 residues are identical. Human cells expressing high levels of an hREV1 antisense RNA grew normally, and were not more sensitive to the cytotoxic effect of 254 nm UV radiation than cells lacking antisense RNA. However, the frequencies of 6-thioguanine resistance mutants induced by UV in the cells expressing antisense hREV1 RNA were significantly lower than in the control (P = 0.01), suggesting that the human gene has a function similar to that of the yeast homolog.